KARAKTER MORFOLOGI ISOLAT Phlebiopsis sp.1 JAMUR PENGENDALI HAYATI YANG POTENSIAL UNTUK Ganoderma philippii - Desy Puspitasari; Arif Wibowo; Sri Rahayu; Istiana Prihatini; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Identification of wood decay fungi based on morphological character of isolates is very helpful where identification of fruit body morphology is ambiguous. Nine isolates of Phlebiopsis sp.1 obtained from the isolation root of Eucalyptus pellita in permanent plots with root rot disease have the potential as biological control for G. philippii. The verification based on ITS sequences of rDNA showed that these isolates were closely related to P. gigantea and P. flavidoalba. The characterisation of morphological was performed on isolates grown on Malt Extract Agar media with sawdust. Based on the macroscopic observation, the isolates were categorized into three different morphotypes: (1). Cottony mycelium from the beginning to the advanced stage, one isolate (Pb5); (2). Cottony at the beginning and then turned into farinaceous to floccose on the advanced stage, 7 isolates (Pb1, Pb2, Pb4, PB6, PB8, Pb9, Pb10); (3). Absent at the beginning and then turned into zonate on the advanced stage, one isolate (Pb11). Morphotype 2 is the dominant group of Phlebiopsis sp.1 isolates, with fine tufts of white mycelium which turned brown on the surface of the colonies. Morphotype 3 has very different morphological characters than other 8 isolates, it has very characteristic concentric circle with different color and texture of each circle. The growth rate of mycelium ranged between 10.70 - 10.85 cm²/day for morphotype 1 and 2; 1.95 cm²/day for morphotype 3.